Triamcinolone Acetonide as an Adjunct to Bevacizumab for Prevention of Corneal Neovascularization in a Rat Model - Hadi Z Mehrjardi; Reza Ghaffari; Mirgholamreza Mahbod; Hassan Hashemi (Journal of Ophthalmic & Vision Research, 2014)
Purpose: To evaluate the short-term effects of a single subconjunctival injection of triamcinolone acetonide as an adjunct to subconjunctival bevacizumab for prevention of corneal neovascularization in rats. Methods: Chemical cauterization was performed in the central cornea of the right eye in 48 male Sprague-Dawley rats (4 eyes were excluded due to perforation and/ or infection). Immediately after the injury, the rats were randomly assigned to four treatment groups: controls (n=10), received subconjunctival injection of 0.02 mL balanced salt solution; group 1 (n=12), received 0.02 mL bevacizumab (25 mg/mL); group 2 (n=11), were treated with 0.02 mL triamcinolone acetonide (40 mg/mL); and group 3 (n=11), received both bevacizumab and triamcinolone acetonide. On days 7 and 14 after cauterization, digital photographs of the corneas were taken and the area of neovascularization was calculated and compared among the study groups. Results: The area of corneal neovascularization in all three treatment groups was less than the controls (P<0.05 for all comparisons). On day 7, the corneal avascular area was largest in group 3 (63%). On day 14, the area of corneal neovascularization in groups 2 and 3 was smaller than that in group 1 (P=0.031 and 0.011, respectively), but the difference between groups 2 and 3 was not statistically significant (P=0.552). Microscopic evaluation of the cornea was compatible with gross findings; inflammation and the number of new vessels was the least in group 3. Conclusion: Triamcinolone acetonide was more effective than bevacizumab in inhibiting corneal neovascularization. Its adjunctive administration to bevacizumab resulted in even better prevention of corneal neovascularization. However, the produced combined effect was less than the sum of their separate effects and did not match additive or synergistic interactions.